Determination of molar mass practicals - Hoare, Peter (The University of Hull)
1. Determination of the molar mass of a volatile liquid using Dumas' method; 2. Determination of the molar mass of a gas using Regnault's method; - takes "typical" 6th form student ca. 1 - 1.5 hours to complete both experiments. Student instruction sheets (apparatus is trivial).